Do corporate governance and gender diversity matter in firm performance (ROE)? Empirical evidence from Jordan - Malek Hamed Alshirah; Faraj Salman Alfawareh; Ahmad Farhan Alshira'h; Ghaith N. Al-Eitan; Tareq Bani-Khalid; Moh'd Alsqour (Economies, 2022)
The aim of this paper was to examine the effect of managerial/board gender diversity and corporate governance structure on firm performance in a Jordanian business environment - a developing economy that has a distinct environment from that of developed economies. The current study focuses on the unique context of an emerging economy (i.e., Jordan). Data were collected from nonfinancial companies listed on the Amman Stock Exchange from 2018 to 2020. Data analysis was carried out using the random-effects estimator, which was considered as the most suitable for this study. The results disclose that female representation on the board of executives of Jordanian companies had a positive but insignificant effect on corporate performance, as measured by the return on equity, indicating that this variable has no effect on the performance of firms in Jordan. Both family ownership and board size had negative significant effects on performance, but for the moderating effect, corporate governance structure had no effect on the relationship among CEO duality, institution ownership, government ownership, independent directors, and firm performance. The current study only focused on Jordanian industrial firms listed on ASE, thus rendering the findings nongeneralizable to other sectors and nations. Further investigations are urged to broaden the context of the study to achieve more enriched findings. Managers can use the findings to achieve a deeper understanding of the way governance structure affects firm performance. Additionally, regulators at the Jordan Securities Commission can attain valuable insight about the adequacy of the current regulations regarding the role of gender diversity and corporate governance structure in Jordan. The current study contributes to the literature concerning the effect of managerial gender diversity and corporate governance structure on performance. Furthermore, this investigation aims to fill the current research gap in the context of Jordan, which is an emerging economy in the Arab region that is under-represented in this field of research.
Keywords: 330; corporate governance; Amman Stock Exchange; gender diversity; performance